Definition de L’adjectif en langues Bantu - Baka, Jean (Afrika Focus, 1998)
In Bantu, as in other language groups, the definition of the adjective depends on the type of criteria that one uses. Some authors make use of morphological criteria, some of syntactic criteria and others of semantic criteria. From this variety of criteria there follows a diversity of definitions. One can reach, nevertheless, a more appropriate definition, by having recourse to the whole set of possible criteria but giving primacy to the syntactic ones. Such definition allows us - on the one hand - to bypass the dichotomy between nouns and pronouns which is founded on a purely morphological criterion « the form of the prefix » and - on the other hand - to restrict the meaning of the word ’adjective’ to a purely semantic notion. KEY WORDS : linguistics, Bantu, adjective